Recurrent depression predicts high leptin concentrations in patients with coronary artery disease over an 18-months follow-up period: Findings from the prospective multicenter randomized controlled SPIRR-CAD Trial - Ladwig, Karl-Heinz; Marten-Mittag, Birgitt; Olliges, Elisabeth; Johar, Hamima; Atasoy, Seryan; Holdenrieder, Stefan; Albus, Christian; Deter, Hans-Christian; Zwaan, Martina de; Fritzsche, Kurt; Jünger, Jana; Petrowski, Katja; et al. (Journal of affective disorders, 2025)
Background - Leptin, an adipokine suspected to play a role in coronary artery disease (CAD), may also be associated with deteriorated mental health. We investigated the prospective impact of recurrent depressed mood (RDM) on heightened plasma leptin levels in CAD patients. - Methods - Derived from the randomized SPIRR-CAD trial, plasma leptin were measured by the Human Leptin DuoSet ELISA at baseline in 539 patients (including 115 (21.3 %) women and 424 (78.7 %) men) and in 373 participants after 18-months follow up (T3). RDM was based on the clinical course from baseline to follow-up assessed by the Hamilton Depression Rating Scale (HAMD). Multivariate binary logistic regression models identified predictors for heightened leptin at T3. - Results - At baseline, highest leptin level (3rd tertile) was associated with type 2 diabetes (p = 0.009), heart failure symptoms (NYHA III) (p < 0.001), female sex and BMI ≥30 (p < 0.001) but not with age and depression. At study endpoint (T3), RDM was associated with a substantially increased risk of experiencing the highest plasma leptin level (OR 2.92 (95 % CI 1.27-6.75)) followed by increased NT-proBNP (the most prominent indicator of CHF) with an OR of 2.73 (1.22-6.11) - both after adjustment for concurrent factors including weight gain (diff BMI T3-T1) over the study period - the latter accounting for an OR of 1.41 (1.17-1.70). - Limitations - Findings are limited to people of Caucasian ancestry which prevents being generalized to other ethnicities. Although relying upon a prospective design, reverse causality cannot be excluded but is unlikely. - Conclusions - In CAD patients, RDM is a significant predictor of heightened leptin -a finding opening room for a new pathway of the psychobiological underpinning of depression on CAD risk.